Rehabilitation with dental prostheses and its influence on brain activity: A systematic review - Costa, Rayanna Thayse Florêncio; de Oliveira Limirio, João Pedro Justino [UNESP]; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas de (Elsevier, 2022)
Statement of problem: The consequences of edentulism depend on its complexity and are far-reaching, but limited evidence regarding its association with neurologic health is available. Purpose: The purpose of this systematic review was to establish the relationship between oral prosthetic rehabilitation and the regional increase in brain activity. Material and methods: This systematic review was registered in the International Prospective Register of Systematic Reviews (CRD42021262247), and the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guideline was followed. Randomized clinical trials, prospective studies comparing the brain activity of patients rehabilitated with and without the use of dental prostheses, and studies that analyzed the human brain by using noninvasive techniques were used as inclusion criteria. The risk of bias in each study was assessed by using the Risk Of Bias In Non-randomized Studies–of Interventions (ROBINS-I). Results: The search was carried out in the PubMed/MEDLINE, Embase, Cochrane Library, and https://clinicaltrials.gov databases up to June 2021. After a search conducted by 2 reviewers, 8 articles were included in the review. A regional increase in blood flow and regional cerebral activity during dental prosthesis use was identified in the studies. Conclusions: A positive association was found between the different types of prosthetic rehabilitation and brain function. Prostheses may preserve and restore neurological health.